Ciliate microzooplankton from the Northeastern Gulf of Mexico. (29th January 2021) - Snyder, Richard A; Moss, Joseph A; Santoferrara, Luciana; Head, Marie; Jeffrey, Wade H
Abstract: Microzooplankton mediate a critical juncture of autotrophic and heterotrophic microbial production in the water column. Taxonomic and ecological work on this group has been substantial, yet few reports exist for the offshore waters of the Gulf of Mexico (GOM). This report focuses on protists in the phylum Ciliophora collected at stations spanning the continental shelf in the northeastern GOM. We hypothesized that patterns of spatial distribution across the region would be west–east along the coast, rather than north–south coastal to offshore, reflecting major freshwater sources. Samples were obtained by 10 µm plankton net for microscopy and by filtration of seawater for DNA extraction and ciliate-specific clone sequencing. Microscopy and molecular analysis recovered 46 and 156 taxa, respectively. Some visually identified taxa were missing from the sequence analysis and sequences from unknown species dominated molecular results. Differences were apparent with both dominant and rare taxa between February and July sampling and across a trophic gradient from coastal influenced stations to those more representative of the offshore environment. This report provides new data on ciliate microzooplankton richness and distribution in the GOM and adds to our understanding of microzooplankton diversity in the ocean.